Pathological Predictors of Shunt Stenosis and Hepatic Encephalopathy after Transjugular Intrahepatic Portosystemic Shunt. (15th November 2016) - He, Fuliang; Dai, Shan; Xiao, Zhibo; Wang, Lei; Yue, Zhendong; Zhao, Hongwei; Zhao, Mengfei; Lin, Qiushi; Dong, Xiaoqun; Liu, Fuquan
Abstract : Background. Transjugular intrahepatic portosystemic shunt (TIPS) is an artificial channel from the portal vein to the hepatic vein or vena cava for controlling portal vein hypertension. The major drawbacks of TIPS are shunt stenosis and hepatic encephalopathy (HE); previous studies showed that post-TIPS shunt stenosis and HE might be correlated with the pathological features of the liver tissues. Therefore, we analyzed the pathological predictors for clinical outcome, to determine the risk factors for shunt stenosis and HE after TIPS. Methods. We recruited 361 patients who suffered from portal hypertension symptoms and were treated with TIPS from January 2009 to December 2012. Results. Multivariate logistic regression analysis showed that the risk of shunt stenosis was increased with more severe inflammation in the liver tissue (OR, 2.864; 95% CI: 1.466–5.592; P = 0.002 ), HE comorbidity (OR, 6.266; 95% CI, 3.141–12.501; P < 0.001 ), or higher MELD score (95% CI, 1.298–1.731; P < 0.001 ). Higher risk of HE was associated with shunt stenosis comorbidity (OR, 6.266; 95% CI, 3.141–12.501; P < 0.001 ), higher stage of the liver fibrosis (OR, 2.431; 95% CI, 1.355–4.359; P = 0.003 ), and higher MELD score (95% CI, 1.711–2.406; P < 0.001 ). Conclusion. The pathological features can predict individual susceptibility to shunt stenosis and HE.